DERMATOLOJİK ACİLLER - ÜNAL, Gaye (Cerrahpaşa Medical Journal, 2014)
Background.- Cutaneous emergency is not so frequent. But some cutaneous adverse drug reactions are frequent, occurring in 3% of hospitalized patients. There are some important diseases as toxic shock syndrome, every cause of erythroderma, angio-oedema and some cutaneous infections, inflammations, collagenous diseases need early diagnosis and convenient management. Otherwise a very large spectrum of autoimmune disorders is subject matter of urgent conditions in dermatological practice.